ANALISA NON PERFORMING FINACING BANK SYARIAH DI INDONESIA TAHUN 2003 – 2013 - Kadafi Imam Sedayu, B61111052 (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT This study aims to examine and analyze the Non Performing Financing of Sharia Banks in Indonesia. This research is important to do because of bad credit has fluctuation. As for some of the factors analyzed in the influence of Non Performing Financing are: Growth of Gross Domestic Product, Inflation, Exchange Rates USD, and  rate of 1 month convensional bank deposit  in Indonesia.  Data analysis methods used in this study is an analysis of Multiple Linear Regression. These results indicated that the growth of Indonesia economy, the exchange rate of USD and rate of  convensional bank deposit  in Indonesia have positive effect and  significant to Non Performing Financing. Inflation has a negative impact to Non Performing Financing but not significant. Key Words: Non Performing Financing, Gross Domestic Product, Exchange Rate, Inflation , Rate of conventional Deposit